Controller Design Method for Stroke Reduction of Micro-actuator in HDD. Issue 2 (2020) - Yabui, Shota; Atsumi, Takenori; Inoue, Tsuyoshi
Abstract: For realizing high information society, recording capacity of the hard disk drives (HDDs) is required to increase. The capacity of the HDDs depends on positioning accuracy of magnetic head which read/write the digital data on disks. To improve the positioning accuracy, the head positioning control system employs a dual-stage actuator system. The dual-stage actuator system is consisting of the voice coil motor (VCM) and the micro-actuator. The micro-actuator has possibility to move accurately the magnetic head in higher frequency. On the other hand, the stroke limitation can be problem for increasing the control bandwidth: improvement of the positioning accuracy. especially, the stroke limitation is a major constraint to compensate for low frequency vibration. There is the tradeoff between the stroke limitation and the positioning accuracy. To overcome the problem, this study proposes the controller design method for stroke reduction of the micro-actuator. The proposed design method can adjust the main working frequency for each actuator. In this system, the VCM can mainly compensate for the low frequency vibration. The micro-actuator mainly focuses on stabilization of the control system in higher frequency, the working doesn't require the large stroke. The effectiveness is verified in the compensation of the representative internal and external vibration. The proposed method can reduce the stroke of the micro-actuator by about 60% with comparison to the conventional design method with keeping the positioning accuracy.